2013
DOI: 10.1080/15598608.2013.772830
|View full text |Cite
|
Sign up to set email alerts
|

Bias Correction Methods for Misclassified Covariates in the Cox Model: Comparison of Five Correction Methods by Simulation and Data Analysis

Abstract: Measurement error/misclassification is commonplace in research when variable(s) can notbe measured accurately. A number of statistical methods have been developed to tackle this problemin a variety of settings and contexts. However, relatively few methods are available to handlemisclassified categorical exposure variable(s) in the Cox proportional hazards regression model. Inthis paper, we aim to review and compare different methods to handle this problem - naïvemethods, regression calibration, pooled estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…More advanced designs and models have been proposed and may be considered in future [16], [22], [23], [24]. Second, statistically speaking, this problem is a special case with measurement error or misclassification in outcomes [25]. However, we are cautious to recommend statistical correction with hard-to-satisfy-or-verify assumptions partly because of non-statistical reason; more data collection about blinding may do more harm than good [20], [21].…”
Section: Discussionmentioning
confidence: 99%
“…More advanced designs and models have been proposed and may be considered in future [16], [22], [23], [24]. Second, statistically speaking, this problem is a special case with measurement error or misclassification in outcomes [25]. However, we are cautious to recommend statistical correction with hard-to-satisfy-or-verify assumptions partly because of non-statistical reason; more data collection about blinding may do more harm than good [20], [21].…”
Section: Discussionmentioning
confidence: 99%
“…Other discussed methods include probabilistic bias analysis [1, 50], Bayesian bias analysis [1, 73, 74], regression calibration [76, 77], modified maximum likelihood [7880], multiple imputation [77, 81], and propensity score calibration [8284] which all also require that appropriate assumptions are met. The review also articulates the research settings when each of these approaches is most appropriate.…”
Section: Methods and Assumptions Necessary To Reduce Bias Due To Missmentioning
confidence: 99%
“…The performance of MI has been compared with other methods, including RC and MR in settings of linear and logistic regression 19,23,28 and Cox regression. 22,29 These authors found that the optimal method depends on the size of the validation subset and degree of measurement error. Shepherd et al 28 noted MI worked well in the setting of correlated covariate and outcome measurement error in the linear model.…”
Section: Ta B L Ementioning
confidence: 99%